Skin and systemic infections in children with atopic dermatitis: review of the current evidence - Lomelí-Valdez, Rodrigo; Orozco-Covarrubias, Luz; Sáez-de-Ocariz, Marimar (Frontiers in Pediatrics, 2025)
Atopic dermatitis is a chronic, pruritic inflammatory skin disorder that affects approximately 2%–42% of children worldwide. Its course is frequently complicated by secondary bacterial, viral, and fungal infections, which can exacerbate disease severity and hinder treatment outcomes. These infections are thought to arise due to a disrupted skin barrier, reduced antimicrobial peptide production, alterations in the skin microbiome, and Th2-dominant inflammatory response. Identifying the most prevalent and pathogenic microorganisms in patients with AD is critical for early diagnosis, effective management, and prevention of complications. This review provides an updated synthesis of current knowledge on the infectious agents implicated in AD pathogenesis, summarizing recent findings on the epidemiology, microbial interactions, and immune mechanisms involved. Furthermore, it provides an overview of the latest therapeutic strategies for managing AD and its associated infections. By integrating recent insights into pathogenesis and treatment, this study offers a comprehensive perspective on the evolving landscape of AD management in children.